2012
DOI: 10.1007/s12307-012-0124-9
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Microenvironment of Human Tumors: General Significance and Clinical Impact

Abstract: Human cancers grow in a microenvironment of stromal, inflammatory and immunocompetent cells which is variable from tumor to tumor. The characterization of the immune contexture, i.e. the type, density and functional orientation of immunocompetent cells, the presence or absence of tertiary lymphoid structures is a major prognostic factor for patients survival and represent a guide and a target for innovative cancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 59 publications
2
84
1
6
Order By: Relevance
“…The presence of tumor infiltrating lymphocytes (TILs) has been associated with an improved prognosis for a number of different tumor types, including colorectal and GCs (19,20). CTL function is closely regulated by the tumor microenvironment, which consists of cancer cells, inflammatory cells, stromal cells and cytokines (21).…”
Section: Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of tumor infiltrating lymphocytes (TILs) has been associated with an improved prognosis for a number of different tumor types, including colorectal and GCs (19,20). CTL function is closely regulated by the tumor microenvironment, which consists of cancer cells, inflammatory cells, stromal cells and cytokines (21).…”
Section: Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
“…It has been observed that frameshiftinduced neopeptides in patients with MSI-high colorectal cancer are effectively recognized by the immune system. The better outcome of these patients is partly related to the high infiltration of activated CD8+ cytotoxic lymphocytes (CTL) and T helper 1 cells (Th1) (19,(100)(101)(102).…”
Section: Mismatch Repair (Mmr) Deficiency and Hypermutation In Gastromentioning
confidence: 99%
“…Interestingly, FOXP3+ T-Reg infiltration into tumour core appears higher in immunosuppressed solid organ transplant recipients and is associated with a worse prognosis -an effect not seen in other cancers 18,19,24,26 .…”
Section: Inflammatory Infiltration Of Cancermentioning
confidence: 95%
“…Dendritic cells monitor for tumour antigens that are later presented via lymph drainage, to T and B lymphocytes 19 .…”
Section: Inflammatory Infiltration Of Cancermentioning
confidence: 99%
See 1 more Smart Citation